Availability of Outpatient Telemental Health Services in the United States at the Outset of the COVID-19 Pandemic - Cantor, Jonathan H. (Med Care, 2021)
BACKGROUND: Since coronavirus disease 2019 (COVID-19) has caused dramatic changes in everyday life, a major concern is whether patients have adequate access to mental health care despite shelter-in-place ordinances, school closures, and social distancing practices. OBJECTIVES: The aim was to examine the availability of telehealth services at outpatient mental health treatment facilities in the United States at the outset of the COVID-19 pandemic, and to identify facility-level characteristics and state-level policies associated with the availability. RESEARCH DESIGN: Observational cross-sectional study. SUBJECTS: All outpatient mental health treatment facilities (N=8860) listed in the Behavioral Health Treatment Services Locator of the Substance Abuse and Mental Health Services Administration on April 16, 2020. MEASURES: Primary outcome is whether an outpatient mental health treatment facility reported offering telehealth services. RESULTS: Approximately 43% of outpatient mental health facilities in the United States reported telehealth availability at the outset of the pandemic. Facilities located in the United States South and nonmetropolitan counties were more likely to offer services, as were facilities with public sector ownership, those providing care for both children and adults, and those accepting Medicaid as a form of payment. Outpatient mental health treatment facilities located in states with state-wide shelter-in-place laws were less likely to offer telehealth, as well as facilities in counties with more COVID-19 cases per 10,000 population. CONCLUSIONS: At the onset of the COVID-19 pandemic, fewer than half of outpatient mental health treatment facilities were providing telehealth services. Our results suggest that additional policies to promote telehealth may be warranted to increase availability over the course of the COVID-19 pandemic.